Reduction of gelatinization temperatures of starch blend suspensionswith supercritical CO2 treatment - Sarker, Md. Zaidul Islam; Noda, Takahiro; Sharif, Khan Mohammad; Alias, Abdul Karim; Smith, Richard Lee (Elsevier B.V., 2014)
Modification of starch blend properties by contact with supercritical carbon dioxide (scCO2) was studied. Potato starch (PS), sweet potato starch (SPS), and cassava starch (CS) were blended with wheat starch (WS) at 15, 25, 50, 75 and 85% (w/w) ratios. For WS, the maximum decrease in gelatinization temperature (TP) was 13 ◦C. The WS–PS and WS–CS blends exhibited a decrease in TP of 13 to 17 ◦C. Reduction in TP by treatment was 10 to 18 ◦C for all blend ratios. Conditions for lowering the starch blend TP were determined to be a minimum contact time of 1 h with scCO2 at 60 ◦C and 20 MPa. Swelling of starch granules that leads to the lowering of TP involves both kinetic and physicochemical factors. Gelatinization of wheat starch blends with scCO2 pressure treatment provides a versatile and non-thermal method for modifying the properties of ingredients used in food processing applications.